Collision Frequency and Energy Transfer Rate in e–He Scattering - Yeldos Seitkozhanov; Karlygash Dzhumagulova; Erik Shalenov; Murat Jumagulov (Applied Sciences)
Using the optical interaction potential between an electron and a helium atom, we have calculated the momentum-transfer cross-section, collision frequency, and energy transfer rate during elastic electron–helium scattering, focusing on energies up to the ionization threshold of helium (24.6 eV). The interaction potential includes static, polarization, and exchange contributions, accurately representing the scattering process in this range. The optical potential method is well-suited for this analysis, as it effectively reduces the complexity of multiparticle interactions while maintaining the essential physics of elastic scattering. The calculated collision frequency as a function of energy exhibits a distinct maximum near 5 eV, consistent with experimental observations, which has not been captured in earlier theoretical studies. The energy transfer rate, derived using the effective collision frequency, demonstrates efficient energy exchange at low electron energies, with a gradual decline as the energy approaches the ionization threshold. These findings offer critical insights into plasma processes in the diverter region of tokamaks, where helium atoms play a significant role, and contribute to modeling energy transport properties such as electron mobility and temperature equilibrium. The results can serve as a valuable reference for plasma simulations and fusion research applications.